Managing Employee Emotions at the Workplace in the Hospitality Industry (Nepalese Journal of Hospitality and Tourism Management, 2022)
This paper explores frontline employees’ experience of managing emotions at their workplaces. The data for this study were collected using semi-structured interviews with fifteen hotel employees in Macao who were either working or had worked previously as frontline staff. The findings of this study reveal the nature and sources of emotional disturbances for hotel employees as well as strategies used by them to manage their emotions at their workplaces. The study also highlights the impacts of repeated controlling of emotions on employees, and the need for policy makers, including the hotel managers and government agencies that regulate hospitality employment, to develop regulations that emphasise these issues.